Analisis Faktor – Faktor Yang Mempengaruhi Pengelolaan Dana Desa (Studi Kasus Pada Desa Di Kecamatan Sayung) - Puput Meilawati; Jaeni Jaeni (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Village funds are funds provided by the central government sourced from tha state revenue and expenditure budget allocated to villages, village funds are transferred through the distruct/city regional income and expenditure budget. Village funds provided to improve insfrastructure andi t is hoped that the government cn advance in all aspects of lagging villages. Good management of village funds can realize the government’s hopes of this research is to show whether accountability, oversight, community participation, and competence of village officials can affect the management of village officials can affect the management of village funds. This study used a quantitative method, this research was conducted in villages in the sayung subdistrict with a total sampel of 150 respondents, consisting of village officials, village consultative bodies, and the community, the sampling technique is purposive sampling. Primary data used by distributing questionnaires. Based on the test results, it can be concludedthat the variables of accountability, supervision, cummunity participation, and competence of village officials simultaneouslt have a significant effect on the management of village funds. Keywords : Accountability, Supervision, Cummunity Participation, Competence of Village officials, and Management of Village Funds